2023
DOI: 10.1088/1367-2630/acb6e9
|View full text |Cite
|
Sign up to set email alerts
|

No circular birefringence exists in a chiral medium: an analysis of single-mode refraction

Abstract: Optical activity is one of the most fundamental phenomena in nature. The existing theoretical description of optical activity is the circular birefringence, proposed in 1825 by Fresnel. It states that the right-handed circularly polarized (RCP) and left-handed circularly polarized (LCP) waves in a chiral medium propagate at different velocities. Here we show that this is not the case. After obtaining the refraction and reflection coefficients of any elliptically polarized wave at the surface of an isotropic ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Then we turn attention to Eq. ( 7) or its solution (12). Now that the Jones vector à describes the state of polarization relative to the Serret-Frenet frame, Eq.…”
Section: Explanation Of Papp and Harms' Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then we turn attention to Eq. ( 7) or its solution (12). Now that the Jones vector à describes the state of polarization relative to the Serret-Frenet frame, Eq.…”
Section: Explanation Of Papp and Harms' Experimental Resultsmentioning
confidence: 99%
“…Allogyric birefringence [8] or circular birefringence [9], which means different propagation velocities or different refraction indices for right-and left-handed circularly-polarized waves, was commonly believed [10,11] to underlie the optical activity. In a previous paper [12], we proved through a logical analysis that there is no circular birefringence in a chiral medium. Meanwhile, we found that the conventional description of the polarization of light in terms of the Jones vector [13] is incomplete.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…(10) as the circular birefringence was to implicitly assume [1,9] that the polarization vector A in expression (3) could be fully replaced with the Jones vector in Eq. (12). Under that assumption, expression…”
Section: Distinguishing Jones Vector From Polarization Vectormentioning
confidence: 98%